Does rising market volatility undermine sector-level diversification in the Nordic equity market? - Hellström,Hugo (2026)
Diversification reduces portfolio risk when assets are imperfectly correlated, yet evidence suggests that correlations rise in turbulent markets and weaken diversification benefits. This thesis examines whether market volatility undermines sector-level diversification in the Nordic equity market and whether any sector remain resilient. Using daily data for ten Nordic sector indices, the analysis applies a regime based design centered on the COVID-19 volatility peak and estimates sector risk exposures with an extended CAPM including changes in implied volatility (ΔVIX), complemented by correlation measures and Fisher r-to-z tests. Results show that sector to market correlations and market betas increase significantly in periods with high volatility for most sectors, indicating deteriorating diversification benefits, while Healthcare displays comparatively stable exposure and no significant correlation increase. The findings imply that diversification in Nordic equities is state dependent and that tilting portfolios towards defensive sectors may help preserve risk reduction during periods of market stress.
Keywords: Sector diversification; Market volatility; Nordic equity market; Time-varying correlations; VIX